Standard test methods for determining hardenability of steel (American Society for Testing and Materials, 2007)
These test methods cover the identification and description of test methods for determining the harden ability of steels. The two test methods include the quantitative end-quench or Jominy Test and a method for calculating the harden ability of steel from the chemical composition based on the original work by M. A. Grossman.